Simple method of purifying humic acids isolated from tropical hemists (peat soil) - Kasim, Susilawati; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad; Yusop, Mohd Khanif (Science Publications, 2008)
The objectives of this study were: To investigate whether a purification period of HA isolated from Hemists peat soils could be reduced and to investigate whether distilled water could be used to purify HA isolated from Hemists peat soils. Standard procedures were used to extract and fractionate HA in a Hemists peat soil. The isolated HA was purified by suspending the HA 50 mL distilled water, centrifuged for 10 minutes, supernatant decanted and the liquor analyzed for K, Ca, Mg and Na by atomic absorption spectrophotometry. The entire procedure was repeated five times after which the purified HA samples were oven dried at 40ÂºC to a constant weight. Washing HA for 5 consecutive times (10 min for each washing) reduced the ash (mineral matter) content of the HA to an acceptance level of 2%. This finding was associated with significant decrease in K, Ca, Mg and Na contents with increased washing time. This observation also suggests that the distilled water used during the purification process served as Bronsted-Lowry acid thereby donating more H+ which may have replaced some of K+, Ca2+, Mg2+ and Na+ at the exchange sites of the HA. The C, carboxylic COOH, phenolic OH, total acidity and E4/E6 values of the purified HA were consistent with standard values, a further indication of the effectiveness of using distilled water in purifying HA from Hemists peat soil. Humic acids isolated from Hemists peat soil can be purified within one hour using distilled water without altering the true nature of HA.